BAHASA INDONESIA SEBAGAI INSTRUMEN BELA NEGARA DI ERA DIGITAL: KAJIAN ECHO CHAMBER DAN DISINFORMASI BERBASIS AI - Nurhalimah Nafisyah; Salwa Kurnia Putri; Perawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines Indonesian language as a digital state defense instrument amid echo chambers and AI-based disinformation in Indonesia. Social media algorithms create personalized information spaces that reduce information diversity and strengthen social polarization. Meanwhile, artificial intelligence technologies such as generative AI and deepfakes increase the spread of misleading content that is difficult to verify. The purpose of this study is to analyze echo chamber dynamics, AI-based disinformation, and the role of Indonesian language in strengthening national identity and information resilience. This research uses a qualitative literature review method by analyzing 25 national journals published between 2021 and 2026 through content analysis. Findings show that algorithmic systems intensify information fragmentation and polarization, while AI accelerates disinformation production and weakens public trust. Indonesian language plays a strategic role in improving digital literacy, communication clarity, and national awareness. The study concludes that Indonesian language is important for digital state defense in facing echo chambers and AI-driven disinformation